"Völkisch" Writers and National Socialism A Study of Right-Wing Political Culture in Germany, 1890-1960 - Tourlamain, Guy (Cultural History and Literary Imagination, 2014)
This book provides a view of literary life under the Nazis, highlighting the ambiguities, rivalries and conflicts that determined the cultural climate of that period and beyond. Focusing on a group of writers - in particular, Hans Grimm, Erwin Guido Kolbenheyer, Wilhelm Schäfer, Emil Strauß, Börries Freiherr von Münchhausen and Rudolf Binding - it examines the continuities in völkisch-nationalist thought in Germany from c. 1890 into the post-war period and the ways in which völkisch-nationalists identified themselves in opposition to four successive German regimes: the Kaiserreich, the Weimar Republic, the Third Reich and the Federal Republic.